2020
DOI: 10.1155/2020/1690178
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Novel Natural Hydroxyapatite Bioceramic by Thermal Decomposition of Waste Ostrich Bone

Abstract: A novel natural hydroxyapatite (HAp) bioceramic was extracted from the ostrich cortical bone by the thermal decomposition method. HAp was characterized by different analytical tools such as thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) analysis, and scanning electron microscopy (SEM). Removal of organic impurities from the bone powder was confirmed by TGA analysis. FTIR spectra of HAp confirmed the presence of the major functional groups such as phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…The PO4 3stretching bands in bovine and caprine bone samples appear at wavelength 1018 and 1010 cm -1 respectively (Malla et al, 2020). The characteristic bands for CO3 2were assigned at 1446, 1409, 872 cm -1 for both bovine and caprine samples.…”
Section: Functional Groups Present In the Bonesmentioning
confidence: 87%
See 2 more Smart Citations
“…The PO4 3stretching bands in bovine and caprine bone samples appear at wavelength 1018 and 1010 cm -1 respectively (Malla et al, 2020). The characteristic bands for CO3 2were assigned at 1446, 1409, 872 cm -1 for both bovine and caprine samples.…”
Section: Functional Groups Present In the Bonesmentioning
confidence: 87%
“…Also, the Amide I and Amide II bands were 1640 and 1543 cm -1 in bovine, and 1636 and 1543 cm -1 in caprine sample respectively, the Amide peaks could be attributed to the presence of protein (Collagen) macromolecules in the raw bones (Al-Sokanee et al, 2009, Bano et al, 2017. The hydroxyl (OH -) band (3568 cm −1 ) was absent in both samples; this may be attributed to the overlapping of impurity bands over the OHband (Malla et al, 2020). Some of the functional groups bands in the two bone samples appeared in the same wavelength while others were in very close wavelength, Table 2.…”
Section: Functional Groups Present In the Bonesmentioning
confidence: 93%
See 1 more Smart Citation
“…10 HAp can be conveniently synthesized by various chemical methods such as sol-gel, 11,12 sonochemical, 13,14 hydrothermal, 15,16 using microwave, 17,18 etc. In addition, various biogenic sources such as birds wastes, e.g., eggshells, 19,20 bones, 21,22 as well as mammalian bones 2,15 and fish bones, 23,24 etc. have been used to isolate HAp.…”
Section: Introductionmentioning
confidence: 99%
“…4,38,39 However, only a few such studies have been reported so far. 4,31,33 Therefore, also as an extension of our recent work concerning the extraction of HAp nano-bioceramic 22 , the objective of this work has been the extraction of naturally ion-doped nano-HAp from the waste buffalo bone and its characterization for its structure as well as antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%